Will testosterone replacement therapy become a new treatment of chronic heart failure? A review based on 8 clinical trials - Wang, Weiwei; Jiang, Ting; Li, Chunyu; Chen, Jun; Cao, Kejiang; Qi, Lian-Wen; Li, Ping; Zhu, Wei; Zhu, Baoli; Chen, Yan (Journal of Thoracic Disease; Vol 8, No 5 (May 01, 2016): Journal of Thoracic Disease, 2016)
Background: According to the present evidences suggesting association between low testosterone level and prediction of reduced exercise capacity as well as poor clinical outcome in patients with heart failure, we sought to determine if testosterone replacement therapy (TRT) improves clinical and cardiovascular conditions as well as quality of life status in patients with stable chronic heart failure (CHF). Methods: We carried out a review based on 8 published clinical trials to determine whether TRT will benefit patients with CHF. Information of exercise capacity, hemodynamic parameters, electrocardiogram indicators, muscle strength, echocardiography guidelines and laboratory indexes were collected to assess clinical outcomes. Results: We found that TRT could improve significantly exercise capacity, muscle strength and electrocardiogram indicators but no significant changes in ejection fraction (EF), systolic blood pressure (SBP), diastolic blood pressure (DBP), N-terminal pro-brain natriuretic peptide (NT-proBNP), tumor necrosis factor-α (TNF-α), high-sensitivity C-reactive protein (hs-CRP) and interleukin-6 (IL-6). Conclusions: High-quality studies are required to better understand the clinical effects of testosterone.